A wide‐band cavity‐backed slot antenna for end‐fire radiation. Issue 1 (January 2016) - Basit, Muhammad Abdul; Wen, Guangjun; Rasool, Nouman; Xiaolin, Xue
ABSTRACT: In this article, an inverted microstrip‐fed cavity‐backed slot antenna is presented. Two slots with unequal lengths and widths are etched on the top broad wall of the cavity where the wall serves as the ground plane of feeding microstrip line. To render the main beam close to exact end‐fire direction an extended metallic plane is placed in front of the antenna. The proposed antenna operates at center frequency of 13 GHz. It is shown that antenna is capable of providing acceptable near‐end‐fire gain and return loss with a fractional bandwidth of 17.7%. The peak simulated gain at a tilt angle of 30° from exact end‐fire direction is 10.2 dB. It was found that the measurement results of the proposed antenna are in close agreement with the simulated ones. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:193–196, 2016